Membranous nephropathy in Schimke immuno-osseous dysplasia - BEREKET, ABDULLAH; ALPAY, HARİKA (SPRINGER, 2006)
Schimke immuno-osseous dysplasia is a rare autosomal recessive multi-system disorder, with clinical features of growth retardation, spondylo-epiphyseal dysplasia, nephrotic syndrome and immunodeficiency beginning in childhood. Here, we report a new case, in a 10-year-old boy with characteristic symptoms of Schimke immuno-osseous dysplasia. The patient presented with short stature and, later, developed nephrotic syndrome and peritonitis. In addition, he had perinuclear anti-neutrophilic cytoplasmic antibody (p-ANCA)-positive arthritis. Renal pathology of the patients with this disease usually show focal segmental glomerulonephritis, whereas our patient had membranous nephropathy, which has not previously been reported.
Keywords: Schimke immuno-osseous dysplasia; membranous nephropathy; spondylo-epiphyseal dysplasia; nephrotic syndrome; growth failure; NEPHROTIC SYNDROME; SPONDYLOEPIPHYSEAL DYSPLASIA; DISEASE